Co and La supported on Zn-Hydrotalcite-derived material as efficient catalyst for ethanol steam reforming. (17th May 2019) - Cerdá-Moreno, C.; Da Costa-Serra, J.F.; Chica, A.
Abstract: Four samples of Zn-hydrotalcite containing different amounts of Co (5, 10, 20, and 30 wt%) have been synthesized and tested in the steam reforming of ethanol. The best results were obtained with the sample containing 20 wt% of Co (20CoHT), with a complete conversion of ethanol and yields to hydrogen close to the equilibrium (73 mol.%). The physicochemical characterization of the samples by DRX, BET area and TPR indicates that the excellent performance exhibited by the sample containing 20 wt% of Co is due to the higher percentage of reduced cobalt and lower crystallite size of metallic cobalt present in this sample (11 nm). Additional studies have been carried out to improve the stability of this catalytic material against deactivation by the incorporation of 1 wt% of La. Stability studies were carried out using an industrial alcoholic waste as feed. Deactivation after 24 h of reaction time was found lower for the catalyst containing La (20CoLaHT), confirming the positive effect of lanthanum on the catalytic stability. The results presented here show that it is possible to prepare a catalyst based on Co supported on Zn-hydrotalcite and promoted with La with improved ethanol conversion, high hydrogen selectivity, and high stability to produce hydrogen by the steam reforming of an industrial alcoholic waste without commercial value. Highlights: Ethanol steam reforming catalysts based on Zn-hydrotalcite with Co have been prepared. High EtOH conversion and H2 selectivity is exhibited by catalyst with 20 wt% of Co. Smaller crystallite size of Co 0 and high reduction degree justify the excellent results. La addition improves the catalytic stability during the reforming of alcoholic wastes.